المسؤولية عن الواجبات الكـفائية المضيعة - كحيل, أسامة (University of Eloued جامعة الوادي, 2019)
تعاني الأمة الإسلامية في زماننا من تقهقر في مجال القوة والتقدم العلمي، بل وتفكك وتناحر، واستضعاف، ويواكب ذلك نقض لكثير من عرا الإسلام، ونأي عن مبادئه في أماكن كثيرة من المعمورة، وقد شرعت الواجبات الكفائية لتحفظ على الأمة مصالحها الدينية والدنيوية، فأردت ببحثي أن اساهم في حث النفوس، وشحذ الهمم لإحياء هذه الواجبات، عبر إدراك أهمية الواجبات الكفائية، واستشعار مدى المسؤولية الفردية عن القيام بها، ومن ثم المساءلة عند التفريط فيها، واشتمل البحث على التعريف بالمسؤولية والواجبات العينية والكفائية وأمثلتها، ثم بيان عموم المسؤولية الشرعية عن الواجبات الكفائية، متبوعا بأسباب تعين المسؤولية عن الواجب الكفائي على فرد أو مجموعة، والأمور التي من شأنها إسقاط التبعة ومن ثم المسؤولية عن فرد أو مجموعة، رغم فوات الواجب الكفائي وتضييع المصلحة المقصودة منه. The Muslim nation suffers in our recent time from regression in the field of power and scientific progress and even disintegration, rivalry, and weakness. This is accompanied by a reversal of many of Islam's covenants and abandonce of its principles in many places of the globe. Therefore, sufficiency duties ( ) have been urged to preserve for the Muslim nation its religious and secular interests. My research aims to contribute to the exhortation of the souls, and to sharpening of the motivations to revive these sufficiency duties by recognizing the importance of these duties and the sense of individual responsibility for doing so and the accountability when abandoned. The research included the definition of responsibility and compulsory and sufficiency duties and their examples as well as a general statement of the legitimate responsibility for the sufficiency duties followed by the reasons that assign responsibility of sufficiency duties for an individual or group and the things that would drop liability and responsibility for an individual or group despite the absence of duty and the loss of the intended interest.
دراسة أصولية
مقال بمجلة الشهاب
Keywords: الواجبات الكـفائية